LETTER OF CREDIT (L/C) SEBAGAI CARA PEMBAYARAN TRANSAKSI PERDAGANGAN INTERNASIONAL DALAM KERANGKA ASEAN ECONOMIC COMMUNITY - , Indah Puji Astuti Utami, Djuwityastuti, Anugrah Adiastuti (PRIVAT LAW II, 2016)
AbstractThis paper aimed and to provide considerations, the use of letters of credit (L/C) as a mean of payment in international trade transactions on the ASEAN economic community. This research is a prescriptive normative legal research. Letter of Credit set in the Uniform Customs and Practice for Documetary Credit 600 (UCP 600). Results The study concluded that, Letter of credit represents a mean of payment in international trade transactions. Payment using this credit is the safest and security for both parties, both parties are importing or exporting. Use of the L/C of import-export activities, particularly in the Asian region predicted will continue to increase due to the existence of regional economic groupings, such as the ASEAN economic community in the ASEAN region. Related to this, then the very suitable L/C are selected and applied as payment when the level of confidence in the beneficiary/applicant/exporter and importer and low-impact for the disadvantaged it high. In the future, in the activities of ASEAN in the region import export can use the L/C as a means of payment.Keywords: Letter of Credit, L/C, payment, international trade transactions, ASEAN Economic Community.Â AbstrakArtikel ini bertujuan untuk untuk memberikan pertimbangan-pertimbangan penggunaan Letter of Credit (L/C) sebagai cara pembayaran dalam transaksi perdagangan internasional pada ASEAN Economic Community. Penelitian ini merupakan penelitian hukum normatif yang bersifat preskriptif. Letter of Credit (L/C) diatur di dalam Uniform Customs and Practice for Documetary Credit 600 (UCP 600). Hasil Penelitian menyimpulkan bahwa L/C merupakan salah satu dari cara pembayaran dalam transaksi perdagangan internasional. Pembayaran dengan menggunakan L/C ini merupakan cara yang paling aman dan memberikan kepastian kepada kedua belah pihak, baik pihak importir ataupun pihak eksportir. Penggunaan L/C dalam kegiatan ekspor impor khususnya di wilayah Asia diprediksi akan terus meningkat seiring dengan adanya kelompok ekonomi regional, seperti ASEAN Economic Community di wilayah ASEAN. Berkaitan dengan hal tersebut, maka L/C sangat cocok dipilih dan diterapkan sebagai pembayaran ketika tingkat kepercayaan di antara beneficiary/eksportir dan applicant/importir rendah dan dampak untuk dirugikan itu tinggi. Sehingga kedepannya, dalam kegiatan ekspor impor di wilayah ASEAN dapat menggunakan L/C sebagai pembayarannya.Kata kunci: Letter of Credit, L/C, cara pembayaran, transaksi perdagangan internasional, ASEAN Economic Community.